Monitoring Processes and Their Neuronal Correlates as the Basis of Auditory Verbal Hallucinations in a Non-clinical Sample - Storchak, Helena; Hudak, Justin; Dresler, Thomas; Haeussinger, Florian B.; Fallgatter, Andreas J.; Ehlis, Ann-Christine (Frontiers in Psychiatry, 2021)
Auditory verbal hallucinations (AVH) are a characteristic symptom of psychosis. An influential cognitive model accounting for the mechanisms in the generation of AVHs describes a defective monitoring of inner speech, leading to the misidentification of internally generated thoughts as externally generated events (Frith, 1992; Frith and Done, 1989). In this study, we utilized an inner speech paradigm during a simultaneous fNIRS-fMRI measurement, in order to replicate the findings of neural correlates of inner speech and auditory verbal imagery (AVI) in healthy subjects, reported in earlier studies, and to provide the first validation of the paradigm for fNIRS measurements. To this end, 20 healthy subjects were required to generate and silently recite first and second person sentences in their own voice (inner speech) and imagine the same sentences in a different, alien voice (AVI). Furthermore, questionnaires were deployed to assess the predisposition to acoustic hallucinations and schizotypal traits to investigate their connection to activation patterns associated with inner speech and monitoring processes. The results showed that both methods, fNIRS and fMRI, exhibited congruent activations in key brain areas, claimed to be associated with monitoring processes, indicating that the paradigm seems to be applicable using fNIRS alone. Furthermore, the results showed similar brain areas activated during inner speech and monitoring processes to those from earlier studies. However, our results indicate that the activations were dependent more on the sentence form and less on the imaging condition, showing more active brain areas associated with second person sentences. Integration of the sentence construction into the model of inner speech and deficient monitoring processes as the basis for the formation of AVHs should be considered in further studies. Furthermore, negative correlations between questionnaires’ scores and activations in precentral gyrus and premotor cortex indicate a relationship of schizotypal characteristics and a deficient activation pattern.